Calpain inhibition ameliorates scald burn-induced acute lung injury in rats. Issue 1 (8th October 2018) - Du, Peng-Ran; Lu, Hong-Ting; Lin, Xi-Xiang; Wang, Li-Feng; Wang, Yan-Xia; Gu, Xiao-Ming; Bai, Xiao-Zhi; Tao, Ke; Zhou, Jing-Jun
Abstract: Background: The molecular pattern of severe burn-induced acute lung injury, characterized by cell structure damage and leukocyte infiltration, remains unknown. This study aimed to determine whether calpain, a protease involved in both processes, mediates severe burn-induced acute lung injury. Methods: Rats received full-thickness scald burns covering 30% of the total body surface area, followed by instant fluid resuscitation. MDL28170 (Tocris Bioscience), an inhibitor of calpain, was given intravenously 1 h before or after the scald burn. The histological score, wet/dry weight ratio, and caspase-3 activity were examined to evaluate the degree of lung damage. Calpain activity and its source were detected by an assay kit and immunofluorescence staining. The proteolysis of membrane skeleton proteins α-fodrin and ankyrin-B, which are substrates of calpain, was measured by Western blot. Results: Time-course studies showed that tissue damage reached a peak between 1 and 6 h post-scald burn and gradually diminished at 24 h. More importantly, calpain activity reached peak levels at 1 h and was maintained until 24 h, paralleled by lung damage to some extent. Western blot showed that the levels of the proteolyzed forms of α-fodrin and ankyrin-B correlated well with the degree of damage. MDL28170 at a dose of 3 mg/kg b. w. given 1 h before burn injury not only antagonized the increase in calpain activity but also ameliorated scald burn-induced lung injury, including the degradation of α-fodrin and ankyrin-B. Immunofluorescence images revealed calpain 1 and CD45 double-positive cells in the lung tissue of rats exposed to scald burn injury, suggesting that leukocytes were a dominant source of calpain. Furthermore, this change was blocked by MDL28170. Finally, MDL28170 given at 1 h post-scald burn injury significantly ameliorated the wet/dry weight ratio compared with burn injury alone. Conclusions: Calpain, a product of infiltrating leukocytes, is a mediator of scald burn-induced acute lung injury that involves enhancement of inflammation and proteolysis of membrane skeleton proteins. Its late effects warrant further study.